Habitat prediction of Shrimp Barong (Panulirus spp) in East Java Waters - Samsul Huda; Siti Naviah (Universitas Muhammadiyah Malang, 2022)
The production of barong shrimp (Panulirus spp) is mostly caught from the sea, although restocking efforts have been initiated, the results have not had an impact. The high demand and its economic value increase the frequency of catching efforts, therefore information on the stock condition of barong shrimp (Panulirus spp) and their distribution habitat is needed to create a sustainable resource. This study aims: to obtain the stock of sustainable potential and the distribution of their habitat in the waters of East Java. The research method uses the Walter-Hilborn model approach, the results conclude that the standard type of fishing gear is Trap, the prediction of potential biomass stock in open access conditions in 2030 is 37,763.64 Kg, the remaining stock in 2030 is 21 percent ( %), sustainable fishing effort 143,2000 trips/year, maximum sustainable catch 45820.15kg/year, fishing power 0.0000004, habitat distribution dominance in Water Management Area 712.